Autophagy and ubiquitin-mediated proteolysis may not be involved in the degradation of spermatozoon mitochondria in mouse and porcine early embryos. Issue 1 (16th December 2014) - Jin, Yong-Xun; Zheng, Zhong; Yu, Xian-Feng; Zhang, Jia-Bao; Namgoong, Suk; Cui, Xiang-Shun; Hyun, Sang-Hwan; Kim, Nam-Hyung
Summary: The mitochondrial genome is maternally inherited in animals, despite the fact that paternal mitochondria enter oocytes during fertilization. Autophagy and ubiquitin-mediated degradation are responsible for the elimination of paternal mitochondria in Caenorhabditis elegans ; however, the involvement of these two processes in the degradation of paternal mitochondria in mammals is not well understood. We investigated the localization patterns of light chain 3 (LC3) and ubiquitin in mouse and porcine embryos during preimplantation development. We found that LC3 and ubiquitin localized to the spermatozoon midpiece at 3 h post-fertilization, and that both proteins were colocalized with paternal mitochondria and removed upon fertilization during the 4-cell stage in mouse and the zygote stage in porcine embryos. Sporadic paternal mitochondria were present beyond the morula stage in the mouse, and paternal mitochondria were restricted to one blastomere of 4-cell embryos. An autophagy inhibitor, 3-methyladenine (3-MA), did not affect the distribution of paternal mitochondria compared with the positive control, while an autophagy inducer, rapamycin, accelerated the removal of paternal mitochondria compared with the control. After the intracytoplasmic injection of intact spermatozoon into mouse oocytes, LC3 and ubiquitin localized to the spermatozoon midpiece, but remnants of undegraded paternal mitochondria were retained until the blastocyst stage. Our results show that paternal mitochondria colocalize with autophagy receptors and ubiquitin and are removed after in vitro fertilization, but some remnants of sperm mitochondrial sheath may persist up to morula stage after intracytoplasmic spermatozoon injection (ICSI).